2001
DOI: 10.1021/ma002223f
|View full text |Cite
|
Sign up to set email alerts
|

H and 13C NMR Spectra of a Hyperbranched Aromatic Polyamide from p-Phenylenediamine and Trimesic Acid

Abstract: The structure of hyperbranched aromatic polyamides synthesized from different ratios of p-phenylenediamine and trimesic acid (A2 + B3 reagent pair) has been investigated by means of 1 H and 13 C NMR spectroscopy. On the basis of a detailed NMR signal assignment six 1,3,5-trisubstituted benzene moieties with different substitution patterns can be distinguished. The different monomer ratios influence the polymer architecture with respect to the content of these substructures, the degree of branching and the pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(81 citation statements)
references
References 12 publications
3
78
0
Order By: Relevance
“…hyperbranched polymer systems because, unlike the equation introduced by Hawker [25] and modified by Kim [26], it is valid for both low and high molecular weight hyperbranched polymers and oligomers. It is also more reliable when monomer feed compositions are varied [6] such as in the experiments reported here.…”
Section: Nmr Assignments and Integrationsmentioning
confidence: 86%
See 3 more Smart Citations
“…hyperbranched polymer systems because, unlike the equation introduced by Hawker [25] and modified by Kim [26], it is valid for both low and high molecular weight hyperbranched polymers and oligomers. It is also more reliable when monomer feed compositions are varied [6] such as in the experiments reported here.…”
Section: Nmr Assignments and Integrationsmentioning
confidence: 86%
“…Deuterated NMR solvent, dimethylsulfoxide-d 6 , was ordered from Cambridge Isotope Laboratories (Andover, MA, USA). HPLC grades of acetone, chloroform, and methanol were purchased from J.T.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In order years to integrate molecular simulations with dynamic to address this issue, a previous study by Oguz and Galanalysis and optimization. One approach is the derivalivan [17] proposed the use of high-dimensional step-step tion of stochastic time evolution equations from the correlation functions, which provided a more detailed probabilistic master equation [11], under assumptions state description of the film surface, compared to the that are mostly applicable for well-mixed reacting syssurface roughness alone. This study demonstrated the tems.…”
Section: Ili Conclusion and Recommendationsmentioning
confidence: 99%